Pemetaan Penelitian Rasio Capital Adequacy Ratio (CAR) pada Perbankan Syariah dan Konvensional: Studi Bibliometrik VOSviewer dan Literature Review - Eka Wahyu Hestya Budianto; Nindi Dwi Tetria Dewi (Magister Akuntansi FB-UK.Maranatha, 2022)
This study aims to determine the research mapping regarding the Capital Adequacy Ratio (CAR) ratio in Islamic and Conventional Banking using a mix-method approach, namely the VOSviewer bibliometric study and literature review. Data analysis techniques include: (1) mapping the distribution of journal publications around the CAR ratio; (2) mapping the results of the VOSviewer bibliometric visualization around the CAR ratio based on the number of clusters and their items; and (3) mapping research topics around the CAR ratio using a literature review study. The results showed that: (1) based on the distribution of journal publications, there were 636 journal publications regarding the CAR ratio; (2) based on the mapping of the VOSviewer bibliometric study, the network visualization results around the CAR ratio are divided into 5 clusters and 217 topic items; (3) based on the mapping of literature review studies, there are 58 topics around the influence of the CAR ratio and 31 topics about the determinants of the CAR ratio. The implications and contributions of this research are to map research topics around CAR ratios in Islamic and Conventional Banking which are often or rarely researched by researchers so that they can be a reference for subsequent researchers.